On the applicability of the cumulative strain energy density for notch fatigue analysis under multiaxial loading. (August 2022) - Branco, R.; Prates, P.; Costa, J.D.; Cruces, A.; Lopez-Crespo, P.; Berto, F.
Highlights: The applicability of fatigue toughness under multiaxial load is explored. A fatigue life prediction model based on fatigue toughness is introduced. The proposed model is formulated within a linear-elastic framework. The model showed better predictive capabilities than other well-known models. Abstract: In this paper, the cumulative strain energy density, also called fatigue toughness, was used to predict the fatigue life of notched members subjected to multiaxial loading. The relationship between the total energy absorbed to fracture and the number of cycles to failure was established from uniaxial strain-controlled fatigue tests. Multiaxial fatigue tests were performed on notched round bars made of high-strength steel under proportional bending-torsion considering different normal stress to shear stress ratios and different loading orientations. The fatigue lives predicted with the proposed model were compared to those obtained with other stress-based and energy-based models. Overall, the proposed model led to good predictions, and showed better predictive capabilities than the other tested models.